Aesthetics of Soundscape Ecology and Music Composition - Gerard, Garrison (The Nordic Journal of Aesthetics, 2025)
Soundscape ecology is a rapidly expanding field that seeks to examine our natural and urban ecosystems through the lens of sonic events. Musicians have explored the overlap between acoustic ecology and music through their own compositions and writing. Soundscape ecologists have shown that the acoustic dimension of an ecosystem is vital to understanding our environment and reveals details not visually apparent. My work builds on these thinkers and practitioners, exploring the bi-directional interplay between soundscape ecology and music composition. In this paper, I examine the aesthetic and ethical considerations of using recorded natural sound in music compositions with a particular focus on silence, ecomimesis, and acoustic ecology. The main vehicle for this discussion is the planning, recording, composition, and presentation of my composition, Ecosystem [512], which takes as its foundational material the sound recordings from a nine-month acoustic survey of Iceland’s National Parks.